If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 4 = 5t + -2 Reorder the terms: 4 + 3t = 5t + -2 Reorder the terms: 4 + 3t = -2 + 5t Solving 4 + 3t = -2 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 4 + 3t + -5t = -2 + 5t + -5t Combine like terms: 3t + -5t = -2t 4 + -2t = -2 + 5t + -5t Combine like terms: 5t + -5t = 0 4 + -2t = -2 + 0 4 + -2t = -2 Add '-4' to each side of the equation. 4 + -4 + -2t = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -2t = -2 + -4 -2t = -2 + -4 Combine like terms: -2 + -4 = -6 -2t = -6 Divide each side by '-2'. t = 3 Simplifying t = 3
| 2c^2+13c+21=0 | | 2+8=j | | b^2+7b+10=0 | | 3.5I=3 | | 3.6=-1.2h | | 3(3x+2)=14x+4-5x+2 | | 6(5z-1)-5(z+2)=11(z+1) | | 9h=-81 | | 8t+2*t-1= | | X^2+14x-10=0 | | 6x+2*-x-3= | | q(t)=(3t+8) | | 5p-3*2p+4= | | 7r+2*8r= | | y+4*y+3= | | z+7*5z-1= | | (z+7)*(5z-1)= | | 10x-6=6x+14 | | x-5*4=56 | | 6.3=9 | | 3x-9=90 | | 200-3x=33x+24 | | 10-10x=22-17x | | 4(8x-8)=30 | | 4y(y+7)=72 | | 62-2x=8x+2 | | x-3x+10=y+4 | | 6x-18=-96 | | c^2=-15-8c | | 12=6n | | Y=(6x+88) | | 2(3x-7)-4=2(x-3)+12 |